2008
DOI: 10.2304/rcie.2008.3.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Overrepresented Minorities in Special Education in the United States and Romania: Comparison between African-American and Roma Populations in Disability Studies

Abstract: This manuscript briefly examines minority participation within the school population that is eligible for special education services -namely, African Americans in the United States and the Roma population in Romania. A large percentage of students from both minorities come to school unprepared to learn and they remain behind because of the simultaneous action of several factors, such as family values, material support for child education, evaluation team members' and teachers' perceptions and expectations, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Higher involvement of Roma parents can also represent another vital dynamic in the process of desegregation: Although Želinský, Gorard and Siddiqui (2021) confirmed that -in comparison to non-Romamany Roma parents express lower levels of educational aspirations for their children, a recent study by Moree (2019) shows that Roma parents are increasingly aware of the education system and that they want either to send their children to a mainstream school or have them in a segregated school, but one with a high quality of education. Walker (2008) also emphasizes that in order to overcome discrimination in education, ethnic minorities should set high expectations for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Higher involvement of Roma parents can also represent another vital dynamic in the process of desegregation: Although Želinský, Gorard and Siddiqui (2021) confirmed that -in comparison to non-Romamany Roma parents express lower levels of educational aspirations for their children, a recent study by Moree (2019) shows that Roma parents are increasingly aware of the education system and that they want either to send their children to a mainstream school or have them in a segregated school, but one with a high quality of education. Walker (2008) also emphasizes that in order to overcome discrimination in education, ethnic minorities should set high expectations for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Cantwell and Bodelius (2005) reported that in Romania, as many as 40% of institutionalized children were Roma, while in Bulgaria, the disproportionate representation was even greater in 2005. I believe that the difference among the estimates of percentages of Roma in Romanian institutions is due to the geographical locations of the institutions and the concentration of Roma population in the region, similar to the phenomenon of overrepresentation of African Americans in the United States in low-track educational programs (see Walker, 2008).…”
Section: A Short History Of Institutionalization During the Communistmentioning
confidence: 93%
“…Some scholars invoke a cultural deficit in making the argument that Roma are 'incapable' of benefiting from formal education. Walker (2010) argues that Romani students have "social and cultural conditions" (176) which leave them unprepared for school. She also argues that Romani students have "cultural needs" (Walker 2008, 400) that prevent educational success.…”
Section: Literature Reviewmentioning
confidence: 99%